Все те незриме світло - Doerr, Anthony, 1973- (4th Estate, 2023)
For Marie-Laure, blind since the age of six, the world is full of mazes. The miniature of a Paris neighbourhood, made by her father to each her the way home. The microscopic layers within the invaluable diamond that her father guards in the Museum of Natural History. The walled city by the sea, where father and daughter take refuge when the Nazis invade Paris. The radio waves that crisscross the air, bringing a long-lost voice and new worlds to her agoraphobic great-uncle. And a life which, unbeknownst to her, takes her ever closer to Werner, a German orphan, destined to labour in the mines until a broken radio fills his life with possibility and brings him to the notice of the Hitler Youth.